SafetyCrown: a patient-centered, fully digital concept for immediate implant restoration following the one-abutment/one-time concept-a pilot case series of a new treatment concept - Lukas Waltenberger; Stefan Wolfart (SpringerOpen, 2022)
Abstract Introduction The patient-centered SafetyCrown-workflow enables the immediate restoration of posterior missing teeth and short free-end situations following one-abutment/one-time within three visits and only one surgical approach. This prosthodontic rehabilitation aims to combine the advantages of cemented and screw-retained restorations. Report The concept has been performed with 4 restorations in 3 patients and followed up for up to 1 year (mean: 11.2 months) without technical and/or biological complication. Visit 1: Intraoral optical impression, CBCT, and tooth shade selection. Virtual implant planning is performed, and a surgical guide is printed. After exporting the planned implant position, a tooth-colored abutment is fabricated from zirconia with a 1-mm supragingival cementation line, adhesively bonded to a titanium base. Visit 2: Fully navigated implant placement with insertion of the definitive abutment. Subsequently, optical impressions are prepared for A: immediate restoration using a PMMA crown without functional contacts; B: definitive crown fabricated from monolithic zirconia and individualized. The localization of the screw channel is marked using stain thus permitting precise screw channel access, if necessary. Visit 3: After osseointegration of the implant, the definitive crown is adhesively cemented supragingival. In a retrospective analysis of PROMs ('How stressful was the treatment process [...]?' (0 = not stressful at all, 100 = very stressful), mean VAS score for SafetyCrown of 14 (SD 11.7) and 29.8 (SD 23.1) for standard procedure were present. Conclusion The SafetyCrown offers a shortened, patient-oriented concept for implant-supported single-tooth reconstructions omitting second-stage surgery. Clinical performance and hypothesized prosthodontic benefits require confirmation via an RCT.